Macrocephaly-cutis marmorata telangiectatica congenita with seizures. Case report and review of the literature. - Atitallah, S.; Krifi, F.; Yahyaoui, S.; Ben Rabeh, R.; Missaoui, N.; Mazigh, S.; Bouyahia, O.; Boukthir, S. (European Journal of Pediatric Dermatology, 2024)
Cutis marmorata telangiectatica congenita (CMTC) is a rare congenital vascular anomaly characterized by a cutaneous reticulated vascular network. Although it is usually isolated, it can sometimes be associated with systemic anomalies, including macrocephaly, a condition termed Macrocephaly-CMTC syndrome (M-CMTC). We report the case of a one-month-old girl diagnosed with M-CMTC, associated with seizures and limb asymmetry. After treatment with antiepileptic drugs and careful follow-up, the patient’s condition improved, with regression of the skin lesions and no further seizures.